Development of gingivitis in rats receiving oral applications of peroxide sunflower oil - Markov, A. V. (Journal of Education, Health and Sport, 2020)
Aim. Determine the condition of the gums in rats receiving oral applications of peroxide sunflower oil (PSO). Methods. PSO was obtained by heating sunflower oil in the presence of Н2О2 at +180°С for 60 minutes. PSO in a dose of 0.5 ml per rat was applied to the oral mucosa for 3 or 5 days. The activity of elastase, urease, lysozyme, catalase and the content of MDA (malondialdehyde) were determined in the gum. The antioxidant-prooxidant API index was calculated by the ratio of catalase and MDA, and the degree of dysbiosis was calculated by the ratio of the relative activities of urease and lysozyme.. Results. After 5 days of PSO applications, an increase in elastase activity, urease, MDA content and the degree of dysbiosis against the background of a decrease in lysozyme activity, catalase and the API index was established. Conclusion. Oral applications of PSO cause a decrease in the level of non-specific immunity, antioxidant defense, an increase in microbial seeding, the degree of dysbiosis and the development of gingivitis.